Chronic intermittent hypoxia accelerates cardiac dysfunction and cardiac remodeling during cardiac pressure overload in mice and can be alleviated by PHD3 overexpression - Xu, Xuan; Zhen, Peng-Hao; Yu, Fu-Chao; Wang, Tao; Li, Sheng-Nan; Wei, Qin; Tong, Jia-Yi (Frontiers in Cardiovascular Medicine, 2022)
Obstructive sleep apnea (OSA) accelerates the progression of chronic heart failure (CHF). OSA is characterized by chronic intermittent hypoxia (CIH), and CIH exposure accelerates cardiac systolic dysfunction and cardiac remodeling in a cardiac afterload stress mouse model. Mechanistic experiments showed that long-term CIH exposure activated hypoxia-inducible factor 1α (HIF-1α) expression in the mouse heart and upregulated miR-29c expression and that both HIF-1α and miR-29c simultaneously inhibited sarco-/endoplasmic reticulum calcium ATPase 2a (SERCA2a) expression in the mouse heart. Cardiac HIF-1α activation promoted cardiomyocyte hypertrophy. SERCA2a expression was suppressed in mouse heart in middle- and late-stage cardiac afterload stress, and CIH exposure further downregulated SERCA2a expression and accelerated cardiac systolic dysfunction. Prolyl hydroxylases (PHDs) are physiological inhibitors of HIF-1α, and PHD3 is most highly expressed in the heart. Overexpression of PHD3 inhibited CIH-induced HIF-1α activation in the mouse heart while decreasing miR-29c expression, stabilizing the level of SERCA2a. Although PHD3 overexpression did not reduce mortality in mice, it alleviated cardiac systolic dysfunction and cardiac remodeling induced by CIH exposure.